Determinan Niat Kecurangan Akademik Dengan Menggunakan Fraud Triangle - Ika Kristianti; Daffa Dwi Setyawan (Journal of Economic, Bussines and Accounting (COSTING), 2021)
This research was conducted with the aim of examining the variables or factors that could influence the intention of academic cheating in the student environment by using the fraud triangle dimension consisting of pressure, opportunity and rationalization. This research was conducted on students of the undergraduate accounting study program at Salatiga City Universities, which consists of the Christian Satya Wacana Salatiga University, the Salatiga State Islamic Institute, and the AMA Salatiga College of Economics. This research was conducted using the snowball sampling method using quantitative methods, both in data collection and analysis. This study can provide empirical evidence if the opportunity and rationalization variables have a positive effect on students 'academic cheating intentions during this online lecture, besides that it was also found that pressure had a negative effect on students' academic cheating intentions. Keywords : Intentions of Cheating, Triangle Fraud, Pressure, Opurtinity, Rasionalization.